2002
DOI: 10.1097/00005650-200202000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inappropriate Drug Use on Mortality and Functional Status in Representative Community Dwelling Elders

Abstract: Identifying the impact of inappropriate drug use may depend on the criteria applied. Further studies are needed that measure additional outcomes and use alternate measures of inappropriate drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
3
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 46 publications
3
92
3
1
Order By: Relevance
“…60,61 Furthermore, the findings of Stuart et al that there was little change in the most commonly used drugs, 20 in conjunction with findings from Briesacher at al., 21 suggest that providers may need additional evidence before they change prescribing patterns. 60,62,63 The inconsistency in findings from studies evaluating outcomes associated with exposure to Beers-criteria drugs based on a dichotomous measure 8,[17][18][19]21 may merely be the result of methodological problems, such as failure to use an incident cohort in analyses or poor ascertainment of the temporal relationship between drug exposure and patient outcome. 64 Thus, an important step in changing prescribing patterns is to provide additional evidence for clinicians by conducting a welldesigned study to assess patient outcomes associated with PIPE exposure as defined by the HEDIS criteria.…”
Section: Ss Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…60,61 Furthermore, the findings of Stuart et al that there was little change in the most commonly used drugs, 20 in conjunction with findings from Briesacher at al., 21 suggest that providers may need additional evidence before they change prescribing patterns. 60,62,63 The inconsistency in findings from studies evaluating outcomes associated with exposure to Beers-criteria drugs based on a dichotomous measure 8,[17][18][19]21 may merely be the result of methodological problems, such as failure to use an incident cohort in analyses or poor ascertainment of the temporal relationship between drug exposure and patient outcome. 64 Thus, an important step in changing prescribing patterns is to provide additional evidence for clinicians by conducting a welldesigned study to assess patient outcomes associated with PIPE exposure as defined by the HEDIS criteria.…”
Section: Ss Conclusionmentioning
confidence: 99%
“…Moreover, findings from extant outcomes studies have not consistently linked PIPE, as defined by a dichotomous measure based on the Beers criteria, to negative patient outcomes. 6,8,[16][17][18][19] The fact that only small changes in prescribing patterns have occurred over time in the most commonly used PIPE drugs (e.g., propoxyphene) 20,21 may indicate inadequate training of physicians in the principles of geriatric practice. 22 Alternatively, it may mean that clinicians put little stock in the Beers criteria.…”
mentioning
confidence: 99%
“…6,7 Inappropriate medication use has been measured using various approaches, such as drug utilization review, [8][9][10][11][12][13][14][15][16] the Medication Appropriateness Index 17 and "drugs-to-avoid" criteria (eg, Beers' criteria). 6,7,18 Of all the various criteria used to evaluate medication prescribing appropriateness, the most widely used and accepted are the criteria developed by Beers.…”
mentioning
confidence: 99%
“…6,7,[18][19][20][21][22][23][24] However, there is a lack of empirical studies of the relationship between medication use factors and health outcomes. 8,[25][26][27] Thus, the objective of this study was to estimate the association between inappropriate medication use and transitions from independent to dependent care environments in older adults.…”
mentioning
confidence: 99%
“…146 One study found that 3234 patients experienced functional status decline and mortality when given an inappropriate drug based on the Beers Criteria. 147 After controlling for covariates, however, the study revealed no association with mortality and inappropriate drug use.…”
Section: Population Assessmentsmentioning
confidence: 77%